(untitled) (Eurasian Medical Research Periodical, 2022)
In the Bukhara region, it is important to feed the bee colony with natural, vitamin-rich feed that accelerates the development of the colony, in addition to accelerating the development of the colony, for the artificial breeding of queen bees in early spring if there is no pollen. Natural nutrients have a positive effect on the development of the bee family and create a solid basis for the artificial breeding of queen bees